Pengaruh Penggunaan ChatGPT Terhadap Motivasi Belajar Siswa Kelas X Jurusan Apat di SMK Negeri 1 Kuningan - Nurhidayatillah, Anisa; Haerudin, Dodi Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid advancement of artificial intelligence has influenced the field of education, where ChatGPT offers opportunities to increase interactivity, flexibility, and personalized learning. This study aims to determine the effect of using ChatGPT on the learning motivation of tenth-grade APAT students at SMK Negeri 1 Kuningan. The research method used was a quantitative approach with a pre-experimental design, involving 36 students selected randomly. Instruments included questionnaires, observation, and interviews, while data were analyzed using paired sample t-tests. The results revealed a significant increase in student motivation after using ChatGPT, showing that AI-based tools can enhance learning engagement. The findings highlight the importance of integrating ChatGPT into vocational education to improve students’ learning motivation and support innovative teaching practices.